Optimized high-performance ITO/Ag/ITO multilayer transparent electrode deposited by RF magnetron sputtering - Ferhati, H.; Djeffal, F.; Benhaya, A. (Superlattices and microstructures, 2019)
This paper presents the optimization, elaboration and characterization of a new TCO (Transparent Conductive Oxides) electrode based on ITO/Ag/ITO multilayer design that enables overcoming the trade-off between the electrical and optical properties. A new hybrid approach combining the investigated design and Particle Swarm Optimization (PSO) technique is conducted with the aim of maximizing the Haacke Figures of merit (FoM). It is found that the optimized ITO/Ag/ITO tri-layered design paves a new path toward achieving a high FoM of 125 × 10−3Ω−1. Such improvement is attributed to the improved light management achieved by the efficient modulation of the Ag sub-layer geometry. Subsequently, the optimized multilayer design is fabricated using RF magnetron sputtering technique. The structural, optical and electrical properties associated with the deposited ITO/Ag/ITO multilayer structure are also analyzed. It is found that the fabricated TCO-based electrode shows a high transmittance over than 94.1% and a low sheet resistance of 4.5Ω × sq−1, which is in good agreement with the theoretical predictions. Therefore, the proposed design methodology based on experiments assisted by PSO metaheuristic approach offers exciting opportunities for bridging the gap between transparency and conductivity characteristics. This makes the elaborated ITO/Ag/ITO multilayer design suitable for high-performance optoelectronic applications. •Highly transparent and low-resistance multilayer electrode is developed.•The electrical and optical properties of IAI electrode were investigated.•IAI structure exhibits improvement over the conventional electrodes.•The maximum FoM is 125 × 10−3Ω−1 for the optimized IAI electrode.